Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.jtbi.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Towards a correct description of zooplankton feeding in models: Taking into account food-mediated unsynchronized vertical migration

Abstract: Complex nature of foraging behaviour of zooplankton makes it difficult to describe adequately zooplankton grazing in models with vertical space. In mean-field models (based on systems of PDEs or coupled ODEs), zooplankton feeding at a given depth is normally computed as the product of the local functional response and the zooplankton density at this depth. Such simplification is often at odds with field observations which show the absence of clear relationship between intake rates of organisms and the ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…On the contrary, mesozooplankton (predator) outbreaks up to the densities where the presence of other foragers could strongly affect individual intake rate are very rare (e.g. [55]). We therefore restrict our analysis to the cases when the predator density is not very high without any substantial loss of generality.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, mesozooplankton (predator) outbreaks up to the densities where the presence of other foragers could strongly affect individual intake rate are very rare (e.g. [55]). We therefore restrict our analysis to the cases when the predator density is not very high without any substantial loss of generality.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the copepod chemical efficiency, we demonstrated that even though copepods with low σ values tend to higher population densities, utilizing infochemicals forms an evolutionarily stable strategy for copepods, and foraging randomly is not the best strategy to adopt. It should also be noted that use of the ideal free distribution assumes copepods have total freedom of movement and knowledge of the entire water column [12], [31]. Copepods can be modelled more realistically through use of a diffusion model with chemotaxis terms [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we emphasize that this study should not be interpreted as denying the importance of age and/or size structuring in population dynamics, in particular when modelling interactions between herbivorous zooplankton and their predators. It is well known that different developmental stages of copepods show distinctly different food intake rates, [47][49] and clearly juveniles cannot produce offspring as was the case model (1)–(2). The same suggestion concerns the population of predators: carnivorous zooplankton and planktivorous fish.…”
Section: Discussionmentioning
confidence: 92%